THE LEARNING AND EDUCATIONAL POTENTIAL OF DIGITAL TOOLS IN HUMANITIES AND SOCIAL SCIENCE - Suleimanova, Olga; Guseinova, Innara; Vodyanitskaya, Albina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The paper focuses onup-to-date cutting-edge digital technologies  that may be  used in teaching university students. The authors suggest distinguishing three types of digital tools, or engines: search tools, research tools and interactive ones. The didactic and research potential of these tools is analysed. The search potential of search engines and text corpora is compared, supported by practical templates which illustrate how the engines are employed to their best.The research potential is assessed on the practical example of semantic experimental research into the difference in the meanings of the words competence vs competency. The Google-supported experiment was elaborated and illustrated against traditional polls of native-speakers, the results of the two showed good concordane which testifies to the reliable  validity of research engines for linguistic experiments. Special attention is paid to interactive engines which are used in the educational context, such as Mentimeter, or supporting an educational blog. The blog  is treated as a powerful tool in promoting academic writing skills in students, their communication skills and a didactical tool used  for sharing professionally relevant information among the students and professors. The blog elements are described.